Colorectal Cancer in Iran: Molecular Epidemiology and Screening Strategies - Dolatkhah, Roya; Somi, Mohammad Hossein; Bonyadi, Mortaza Jabbarpour; Asvadi Kermani, Iraj; Farassati, Faris; Dastgiri, Saeed (Journal of Cancer Epidemiology, 2015)
Purpose. The increasing incidence of colorectal cancer (CRC) in the past three decades in Iran has made it a major public health burden. This study aimed to report its epidemiologic features, molecular genetic aspects, survival, heredity, and screening pattern in Iran. Methods. A comprehensive literature review was conducted to identify the relevant published articles. We used medical subject headings, including colorectal cancer, molecular genetics, KRAS and BRAF mutations, screening, survival, epidemiologic study, and Iran. Results. Age standardized incidence rate of Iranian CRCs was 11.6 and 10.5 for men and women, respectively. Overall five-year survival rate was 41%, and the proportion of CRC among the younger age group was higher than that of western countries. Depending on ethnicity, geographical region, dietary, and genetic predisposition, mutation genes were considerably diverse and distinct among CRCs across Iran. The high occurrence of CRC in records of relatives of CRC patients showed that family history of CRC was more common among young CRCs. Conclusion. Appropriate screening strategies for CRC which is amenable to early detection through screening, especially in relatives of CRCs, should be considered as the first step in CRC screening programs.